The role of 5s in improving Occupational Safety and Health Management System (OSHMS) in Small and Medium Enterprises (SMEs) - A Rhaffor, Kauthar; Jamian, Rahim (FAZ Publishing, 2020)
Issues related to occupational safety and health (OSH) in small and medium enterprises (SMEs) are not commonly discussed in research conducted in Malaysia. However, with the high number of workplace accidents contributed by SMEs, the initiatives set up by the government and other related parties seem not adequate to help their enterprises in managing OSH. The big question that surrounds this issue; What is the best approach or intervention that suits the nature of SMEs? This paper reviewed the studies conducted by researchers in OSH field focusing on SMEs, specifically in Malaysia. The review aimed on recommending 5S, one of the most popular improvement techniques in Lean Manufacturing, as the method to help SMEs in improving the way they manage OSH. The practice of 5S is known as a low-cost method that utilizes minimal resources. The implementation of 5S is always associated with the improvement of productivity and efficiency. There are very limited studies focusing on the impact of 5S towards the improvement of OSH management and reduction of workplace accidents. Thus, this paper included the review on previous studies highlighted on 5S as the mean to improve OSH issues in workplace.